Romancing Tropicality: Ilustrado Portraits of the Climate in the Late Nineteenth Century - Aguilar, Jr. (Archīum Ateneo, 2016)
In contrast to the literature’s dominant focus on Western constructions of tropicality, thisarticle explores representations of the tropics by the colonized, specifically the climatological conditions of the Philippines as portrayed in the late nineteenth century by the Europe-based native intellectuals known as ilustrados. Their anticolonial sentiment was intertwined with visceral estrangement from Spain and idealized views of the tropics, which reversed the colonizers’ racial-geographic prejudice and asserted an identity as a civilizable tropical people capable of genius. Rizal’s return visit to the homeland in 1887, however, made him agree with the Spanish premise about the climate in order to argue that colonial rule was the greater disaster.Keywords: tropics • climate • disasters • racism • indolence • nationalism